The Potential of Constructive Journalism Ideas in a Croatian Context. (3rd July 2018) - Kovacevic, Petra; Perisin, Tena
Abstract : This study examines the potential of constructive journalism ideas and their implementation in Croatia, a country with a different social, cultural and historical background than that of Denmark or other Western European countries where constructive journalism is practised. Three Croatian linguists explain the potential hidden meanings of the word constructive for Croatians. Fifteen broadcast journalists and editors in Croatia have been interviewed in order to examine the potential opportunities and obstacles for the implementation of constructive journalism ideas in their newsrooms. Croatian journalists have a more active approach towards journalism and their overall impression of constructive journalism ideas is positive. Both linguists and journalists noticed potential ideological connotations of the word constructive, while journalists were careful about reporting on possible solutions and things that would work so as not to cross the line and be pulled into ideology. When it comes to implementation, most journalists point out differences in mindset, political influences and newsroom routines as main obstacles. A development of a specific strategy for Croatian newsrooms that moves away from adhering to ideas only is recommended, while the word constructive may be used only if it is clearly defined.